PHÁT TRIỂN BỀN VỮNG VÀ PHÁT TRIỂN CON NGƯỜI TRONG KẾ HOẠCH PHÁT TRIỂN KINH TẾ-XÃ HỘI Ở VIỆT NAM HIỆN NAY - Hằng, Trương Thị Thúy (Trung tâm Nghiên cứu Tài nguyên và Môi trường, 2016)
Sustainable development and human development have increasingly become issues attracting the attention of policy makers in all countries. Many research activities have been implemented at national and local levels in Vietnam related to sustainable and human development. However, practice shows that to date these areas still face many difficulties. Using the results of Ministry research in 2007-2008 into “The approach of the goal of human development in the socio-economic plan for sustainable development of Vietnam,” carried out by the Institute of Human Studies in the Vietnam Academy of Social Sciences, this article considers various issues in order to answer certain questions regarding the socio-economic plan in Vietnam today, in particular the degree of interest shown in issues of sustainable and human development.